The equation for annual interest is A = P(1 + r)^t. We can plug in the known information and get A = 16,000(1 + (0.06))^3.5. Next, we can simplify this equation to A = 16,000(1.06)^3.5. Finally, we raise 1.06 to the power of 3.5 and multiply that by 16,000 and get an answer of $19,619.62.
Hope this helps!
Answer:
x=-3
y=26
Step-by-step explanation:
Answer:
h = -7
Step-by-step explanation:
Given:
-49 = 7h
Divde both sides by 7:
-7 = h
Check:
-49 = 7h
-49 = 7(-7)
-49 = -49 ✅
Because 0 + 27 is 27 and 10 + 17 is 27 as well
Answer is 8
Work Shown:
f(x) = sqrt(5*x + 4)
f(12) = sqrt(5*12 + 4) ... replace every x with 12
f(12) = sqrt(60 + 4)
f(12) = sqrt( 64 )
f(12) = 8